INTERNET LANGUAGE AND WORDS IN SOCIAL NETWORKS - Toshtemirova Dilobar Botirbek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the evolution of language influenced by the rapid development of the internet with a particular focus on the emergence of new words and expressions in social networks.This paper analyzes widely used terms, acronyms, emojis, hashtags, and other digital language tools, their integration into daily speech.